The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/cam4.1728
|View full text |Cite
|
Sign up to set email alerts
|

Cancer patients as frequent attenders in emergency departments: A national cohort study

Abstract: BackgroundCancer patients contribute significantly to emergency department (ED) utilization. The objective of this study was to identify factors associated with patients becoming ED frequent attenders (FA) after a cancer‐related hospitalization.MethodsA retrospective cohort study was conducted using national administrative, billing, and death records of Singapore residents discharged alive from Singapore public hospitals from January 2012 to December 2015, with a primary discharge diagnosis of cancer. Patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 30 publications
3
19
1
Order By: Relevance
“…Patients receiving less housing subsidies (3‐3.9 [OR, 0.34; 0.16‐0.71] and ≥4 [OR, 0.37; 0.19‐0.73]) were less likely to be an FA (Table ). These findings were similar to our previous study …”
Section: Resultssupporting
confidence: 94%
See 4 more Smart Citations
“…Patients receiving less housing subsidies (3‐3.9 [OR, 0.34; 0.16‐0.71] and ≥4 [OR, 0.37; 0.19‐0.73]) were less likely to be an FA (Table ). These findings were similar to our previous study …”
Section: Resultssupporting
confidence: 94%
“…In this study, we found that these factors associated with an increased risk of FA status: lower SES (housing subsidy type) and greater comorbidity. This was similar to the findings from other studies …”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations